The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/cncy.20006
|View full text |Cite
|
Sign up to set email alerts
|

Synovial sarcoma: Diagnosis on fine‐needle aspiration by morphology and molecular analysis

Abstract: BACKGROUND: Synovial sarcoma (SS) is characterized by the t(X; 18) (p11.2; q11.2) translocation resulting in the SYT-SSX fusion transcript, detectable by reverse transcriptase polymerase chain reaction (RT-PCR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
(35 reference statements)
2
18
0
Order By: Relevance
“…Synovial sarcomas (SS) are rare soft tissue sarcomas that usually arise near large extremity joints, especially knee joint [4]. SS may pose difficult diagnostic challenges on cytology when encountered as a monophasic variant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synovial sarcomas (SS) are rare soft tissue sarcomas that usually arise near large extremity joints, especially knee joint [4]. SS may pose difficult diagnostic challenges on cytology when encountered as a monophasic variant.…”
Section: Discussionmentioning
confidence: 99%
“…SS presents most usually as a slow-growing deep seated mass, and in half of the cases they are painful [3]. SS could arise from any anatomic site, however, most commonly arise near large extremity joints, especially knee joint [4]. SS have three main histologic patterns: Biphasic synovial sarcoma (BSS); Monophasic synovial sarcoma (MSS); and poorly differentiated synovial sarcoma (PSS) [5].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Sun et al21 showed that the efficiency of FISH is comparable to or even higher than that of RT‐PCR for SYT‐SSX detection. In a recent retrospective and prospective study, Srinivasan et al evaluated the applicability of RT‐PCR looking for the SYT‐SSX transcript on FNAs 22…”
Section: Discussionmentioning
confidence: 99%
“…Because SMARCB1 , located on 22q12, is considered to be a tumor‐suppressor gene, its quasi‐systematically biallelic inactivation, detected at the molecular level, is closely linked to this protein extinction. Aberrations of chromosomes 22 have been reported, and this suggests the presence of a muted SMARCB1 / INI1 suppressor gene at this locus …”
Section: Fna Diagnostic Aspects Combined With Molecular Informationmentioning
confidence: 92%
“…Aberrations of chromosomes 22 have been reported, and this suggests the presence of a muted SMARCB1/ INI1 suppressor gene at this locus. 42,48 ASPS occurs in adolescents and young adults with a predilection for females, and the more common sites of involvement are muscles and soft tissues of the extremities. 49,50 Cells in ASPS display abundant, clear to finely vacuolated cytoplasm, often with disrupted margins and flowing of the cytoplasmic material, prominent nucleoli, and scattered bare nuclei.…”
Section: Epithelioid Tumorsmentioning
confidence: 99%